Early sicca syndrome diagnosis in rheumatoid arthritis - Rotbart-Fiedor, Małgorzata; Wisłowska, Małgorzata (Reumatologia/Rheumatology, 2007)
Sjögren syndrome, called sicca syndrome, is a chronic inflammatory autoimmune disorder characterised by lymphocyte infiltration of exocrine glands, notably the lachrymal and salivary glands. This inflammation causes dryness of the eyes (xeropthalmia) and of the mouth (xerostomia). The aim of the study was to evaluate possibilities of early sicca syndrome diagnosis in rheumatoid arthritis (RA) patients based on histopathological bioptates of labial salivary glands. Subjective dryness symptoms of Sjögren syndrome were confirmed in histopathological examinations in 77% of RA patients.